Architectural knowledge sharing approaches: a survey research - Parizi, Reza Meimandi; Abdul Ghani, Abdul Azim (Asian Research Publication Network, 2008)
Research on software architecture from different perspectives has been done for several years. However, Architectural Knowledge (AK), a relatively new field, has gained its increasing interest among the community. On this regard, various topics devoted to architectural knowledge, such as reusing, sharing, managing, and communicating are being studied. Among them, AK sharing brings new effective challenges and issues not present when studying other topics in architectural knowledge. Therefore, this paper surveys the current researches on AK sharing (pertaining to software architecture), the approaches, models that are being proposed, and issues that arise when sharing different AKs by different parties. By making survey on AK sharing approaches, a better understanding of these approaches and issues related in this area is provided so that it can be a penetrative resource for a fast training and educating in this area of SE. In addition, conclusion about current state of research in this area and future trends for AK sharing is identified.